Pengembangan Metode Analisis Penetapan Kadar Deksklorfeniramin Maleat Sediaan Tablet Secara Kromatografi Cair Kinerja Tinggi Detektor UV - Lilik Budiati; Nurul Ilmiyati (Eruditio : Indonesia Journal of Food and Drug Safety, 2024)
Dexchlorpheniramine maleate, an antihistamine for allergy treatment, is traditionally tested in tablet form using the UV spectrophotometric method referenced in United States Pharmacopeia (USP), NF 43. However, this method struggles to separate the active compound from other tablet components, such as dyes, necessitating an extraction process. Extraction has several drawbacks, including high waste production, extensive use of costly pure solvents, prolonged preparation times, and reliance on hazardous volatile solvents. This study aims to develop a safer, more efficient, and effective method using high-performance liquid chromatography (HPLC), modified from the USP, NF 43 standard. The experimental approach involves method development and validation, focusing on selectivity, precision, accuracy, linearity, and robustness. The selectivity test demonstrated a resolution value 19.6 between dexchlorpheniramine and maleic acid peaks. The specificity test confirmed identical retention times and spectra between standard and sample peaks. Precision testing yielded a relative standard deviation (RSD) below 0.37%. Accuracy tests at 80%, 100%, and 120% levels achieved an average recovery of 99% within the 97%–103% acceptance range. Linearity testing resulted in a correlation coefficient (r) 1.00 and Vx0 of 0.1. ANOVA test results on Robustness testing revealed no significant differences with column modification but identified sensitivity to pH and mobile phase composition changes. In conclusion, the developed HPLC method meets validation parameters, providing a reliable alternative for analyzing dexchlorpheniramine maleate tablets, with attention to pH and mobile phase suitability.